Cryptic temporal changes in stock composition explain the decline of a flounder (Platichthys spp.) assemblage. (21st January 2019) - Momigliano, Paolo; Jokinen, Henri; Calboli, Federico; Aro, Eero; Merilä, Juha
Abstract: Unobserved diversity, such as undetected genetic structure or the presence of cryptic species, is of concern for the conservation and management of global biodiversity in the face of threatening anthropogenic processes. For instance, unobserved diversity can lead to overestimation of maximum sustainable yields and therefore to overharvesting of the more vulnerable stock components within unrecognized mixed‐stock fisheries. We used DNA from archival (otolith) samples to reconstruct the temporal (1976–2011) genetic makeup of two mixed‐stock flounder fisheries in the Åland Sea (AS) and the Gulf of Finland (GoF). Both fisheries have hitherto been managed as a single stock of European flounders ( Platichthys flesus ), but were recently revealed to target two closely related species: the pelagic‐spawning P. flesus and the newly described, demersal‐spawning P. solemdali . While the AS and GoF fisheries were assumed to consist exclusively of P. solemdali, P. flesus dominated the GoF flounder assemblage (87% of total) in 1983, had disappeared (0%) by 1993, and remained in low proportions (10%–11%) thereafter. In the AS, P. solemdali dominated throughout the sampling period (>70%), and P. flesus remained in very low proportions after 1983. The disappearance of P. flesus from the GoF coincides in time with a dramatic (~60%) decline in commercial landings and worsening environmental conditions in P. flesus' northernmost spawning ground, the Eastern Gotland Basin, in the preceding 4–6 years. These results are compatible with the hypothesis that P. flesus in the GoF is a sink population relying on larval subsidies from southern spawning grounds and the cause of their disappearance is a cessation of larval supply. Our results highlight the importance of uncovering unobserved genetic diversity and studying spatiotemporal changes in the relative contribution of different stock components, as well as the underlying environmental causes, to manage marine resources in the age of rapid anthropogenic change.